Multiple Stakeholders' Perspectives on Respite Service Access for People With Dementia and Their Carers. (12th July 2019) - O'Shea, Emma; Timmons, Suzanne; O'Shea, Eamon; Irving, Kate
Abstract: Background and Objectives: People with dementia and carers do not always access respite services in a timely manner, or in some cases, at all. Although carers' perspectives on respite access have been explored, other stakeholder perspectives, especially providers and people with dementia, are underrepresented in the existing literature. The aim of this study was to synthesize multiple stakeholders' perspectives, including people with dementia, on accessing respite services in the context of dementia. Research Design and Methods: Purposive maximum variation sampling was used. Semi-structured interviews were conducted with 35 key stakeholders, including people with dementia ( n = 6), carers ( n = 9), respite frontline staff ( n = 4), respite managers ( n = 8), primary care professionals ( n = 3), and policy-makers/academics ( n = 5). The process of consent is outlined. Data were interpreted inductively using thematic analysis. Reflexivity was considered throughout the research process. Results: Three themes ("Service Acceptability, " "Navigational Knowledge and Skills, " "Constructing and Adjudicating Respite Need") were identified that relate to how access to respite services is negotiated between service providers and dyads. Discussion and Implications: A number of the findings support previous research; however, novel findings discussed relating to the access negotiation process include (a) the ambiguous legitimacy of respite needs, in a system configured to deliver a biomedical model of care and which considers nonmedical care as a family responsibility, and (b) the constraining effects of disparate conceptualizations of "respite" between carers and providers. Future research should interrogate the appropriate boundaries of public responsibility in relation to respite service planning/delivery for dementia, with particular reference to client preferences for community and in-home provision.